The truth is told in various ways - Botero, Juan J. (Estudios de Filosofía, 2008)
This reflection has a specific motivation and that it is necessary to mention because it explains the approach and the questions that are going to be raised here. In Colombia, a political-judicial model was adopted to try to overcome a problem of violence and violation of the elementary norms of social coexistence that has affected its population for decades. It is not really a problem, but, we could say, a family of problems, but the model has been designed to suit it. This model is embodied in the so-called "Law of Justice and Peace" (Law 975 of 2005), "by which provisions are issued for the reincorporation of members of armed groups organized outside the law, who effectively contribute to the achievement of national peace, and other provisions are dictated for humanitarian agreements ". The law regulates issues related to the investigation, prosecution, punishment and judicial benefits of persons linked to the aforementioned groups who demobilize and contribute "to national reconciliation." Article 4 establishes that the reconciliation process to which the law gives rise must "promote, in any case, the right of the victims to truth, justice and reparation." My interest at this point is limited to the "truth" element contained there. [Fragment]